2012
DOI: 10.1542/peds.2011-0838
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity Trends in Children’s Dental Visits: US National Health Interview Survey, 1964–2010

Abstract: We demonstrate a dramatic narrowing of African American/white disparities in 2 measures of children's receipt of dental services from 1964 to 2010. Yet, much more needs to be done before persistent racial disparities in children's oral health status are eliminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
4
15
0
2
Order By: Relevance
“…In 2010, the National Health Interview Survey found that African-American and Caucasian children age 2 to 17 years had similar rates of dental visits in the past year [1]. However, like our study, many other studies have found less dental care in African-American children and adults when compared with Caucasians [7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In 2010, the National Health Interview Survey found that African-American and Caucasian children age 2 to 17 years had similar rates of dental visits in the past year [1]. However, like our study, many other studies have found less dental care in African-American children and adults when compared with Caucasians [7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 51%
“…A US study in 2010 found that 22% of children age 2 to 17 years had not seen a dentist in the past year and that 11% in that age group had never seen a dentist [1]. For over ten years, the American Academy of Pediatric Dentistry and the American Academy of Pediatrics have recommended that infants should visit the dentist when the first tooth appears or no later than one year.…”
Section: Introductionmentioning
confidence: 99%
“…Around 80% of children and adolescents have had a dental visit within the past 12 months [98]. While racial and ethnic disparities in dental visits have been significant in the past, recent data show that such differences have been attenuated substantially [98].…”
Section: Other Alternative Settingsmentioning
confidence: 99%
“…While racial and ethnic disparities in dental visits have been significant in the past, recent data show that such differences have been attenuated substantially [98]. The high access to adolescents may make dental practices worth considering as a setting for HPV vaccine provision.…”
Section: Other Alternative Settingsmentioning
confidence: 99%
“…52 Ainda em relação à temporalidade, somente um dos estudos foi do tipo longitudinal 26 . Houve estudos que compararam sucessivas análises transversais 10,21,26,26,30,34,35,40,42,46,48,51 , um estudo foi descrito como longitudinal do tipo antes e depois 36 e outro estudo descrito como longitudinal 45 , mas após a leitura completa dos textos foi constatado tratar-se de séries de estudos transversais. Portanto, há, nessa revisão, carência de estudos capazes de atribuir fatores causais à demanda por serviços odontológicos.…”
Section: Discussionunclassified